The complete mitochondrial genome sequences of Brassica napus varieties NY18 and 088018. Issue 4 (3rd April 2021) - Zhou, Xiaoying; Chen, Song; Fu, Sanxiong
Abstract: Brassica napus variety NY18 and 088018 are female and male parents of the national registered variety Ningza 1818, respectively. Here, we determined the complete mitochondrial genomes of these two varieties. The genome sizes of NY18 and 088018 were 221, 864 bp and 222, 015 bp, respectively. Both genomes contained 40 protein-coding genes, 21 tRNA genes, and three rRNA genes. Considerable structural variations existed between the two mitochondrial genomes, which were separated into five syntenic regions. Phylogenetic analysis using the maximum-likelihood method showed that the mitochondrial sequences of B. napus were closely clustered, forming a single clade which had a relatively close relationship with the clade formed by B. rapa, B. juncea, and B. oleracea .